Peningkatan Pengetahuan Melalui Edukasi Kesehatan Tentang Pentingnya Pencegahan Anemia Pada Remaja di Mts. Al-Muhajirin Ambon - Rahma Tunny; Fitria Umagapi; Asih Dwi Astuti (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Anemia is one of the problems in adolescents in Indonesia. Anemia is more common in female adolescents than male adolescents. The purpose of this community service activity is to determine the level of adolescent knowledge about anemia and the importance of preventing anemia. The methods in community service activities include providing pretests and posttests, health education about anemia, the importance of preventing anemia. Community service activities use media in the form of leaflets, powerpoint presentations and videos. Knowledge measurement with questionnaires. This activity was carried out at Mts Al-Muhajirin Ambon class IX with 45 students. The results of the activity showed an increase in knowledge based on the results of the posttest, namely 73.4% of students had good knowledge about anemia. In conclusion, health education for adolescents through leaflets, powerpoint presentations and videos can increase knowledge for adolescents at Mts Al-Muhajirin Ambon. This activity needs to be improved by coordinating with the school and local health center to carry out continuous follow-up activities. The need for the formation of peer groups or health information corners at schools in increasing efforts to prevent anemia in adolescents.